Henoch-Schonlein Purpura in an Adult 53 years old - Pelechas, E.; Kavvadias, A.; Tsigaridas, N.; Karagianni, P.; Tsapogas, P. (Archives of Clinical and Medical Case Reports, 2017)
Henoch-Schönlein Purpura (HSP) is a systemic leukocytoclastic vasculitis often noted as a skin rash with skin lesions such as petechiae and palpable purpura. A 53-year-old man presented with a 5-day history of eruptions on his legs and right arm that were mildly pruritic. The lesions were palpable and had been preceded by 10 days of a mild upper respiratory tract infection. The patient did not have any arthralgias, haematochezia or abdominal pain but only a weight reduction during the last 4 months. The diagnosis of HSP has been confirmed by histologic evaluation that revealed leukocytoclastic vasculitis with IgA immune deposits on the vessel walls. Patients with skin rashes must be investigated thoroughly for the prevention of any secondary complications of the disease.